Childhood immersion in the consumer culture: brand loyalty - Liébana Checa, José Antonio; Real Martínez, Santiago; Gutiérrez Urquiza, Fuensanta (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2014)
The present work analyses how advertising works, from a critical perspective. Advertising is used not only as a tool for selling products but also as a platform that fosters certain lifestyles and ways of thinking – in short, as a vehicle for ideological concepts. The arguments presented in the work are based on research carried out in the Spanish city of Ceuta, located in North Africa, amongst boys, girls and adolescents, using different questionnaires to study issues of brand recognition and slogan recall. A core theme of the work is how childhood and adolescence are used in advertising, which is linked to the aim of creating brand loyalty. Boys and girls of just five years old already recognise and recall a large number of brands, albeit fewer slogans; they live in a visual society that is dominated by images. What is more, this is a society in which it is important to advertisers to create homogeneous groups, with similar tastes. The media via which advertising is conveyed are many and diverse, but it is television that stands out in particular, thanks to its omnipresence in every-day life. It is important, therefore, to continue researching these issues and, as a priority, to provide education within schools on the advertising strategies employed, so that young people are made aware of the different ways in which they are being manipulated.
Keywords: Marketing; socialization; childhood; adolescence; brand